2002
DOI: 10.1094/pdis.2002.86.6.599
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Etiology of Brown Apical Necrosis on Persian (English) Walnut Fruit

Abstract: In 1998, a severe fruit drop was observed in Italy, principally on cv. Lara Persian (English) walnut (Juglans regia). Dropped fruit showed a brown patch at the blossom end and blackening and rot of inner tissues. The disease, called brown apical necrosis (BAN), was investigated on fruit collected in Italy and France in 1999. In 2000, studies were carried out in three walnut orchards located in Italy and in France to substantiate the etiology of BAN. Isolations performed from inner diseased fruit tissues yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…This description matches with the symptoms found in fruits with brown apical necrosis from cultivars of Italy, described by Belisario et al [7]. Although necrosis at the apical end is always present, there is no definite correlation between the extent of external and internal lesions [7].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…This description matches with the symptoms found in fruits with brown apical necrosis from cultivars of Italy, described by Belisario et al [7]. Although necrosis at the apical end is always present, there is no definite correlation between the extent of external and internal lesions [7].…”
Section: Introductionsupporting
confidence: 88%
“…With respect to internal symptoms, the infection progresses through the tissues and can reach the seed, causing a brown or black rot of the seeds [6,8]. This description matches with the symptoms found in fruits with brown apical necrosis from cultivars of Italy, described by Belisario et al [7]. Although necrosis at the apical end is always present, there is no definite correlation between the extent of external and internal lesions [7].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous studies showed that X. arboricola pv. juglandis has been also isolated from tissues affected by brown apical necrosis (29)(30)(31). Hajri et al (10) reported the association of X. arboricola pv.…”
mentioning
confidence: 99%